Each question is worth 7 points

Time allowed is 4 hours

No books, notes or calculators permitted

Write full proofs with your answers

**1)** Find all real numbers \(a\) such that there are four different real numbers \(x\) satisfying the equation

\[x(x+1)^3=(2x+a)(x+a-1).\]

**2)** Find all functions \(f:\mathbb{R} \rightarrow \mathbb{R}\) such that for \(x, y \in \mathbb{R}\) we have

\[f(x f(y) + x) = xy+f(x).\]

**3)** Suppose that \(x\), \(y\) and \(z\) are real numbers satisfying the following three equations.

\[\begin{align} x+y+z &=2\\ x^2 +y^2 + z^2 &=6\\ x^3+y^3+z^3&=8 \end{align}\]

Find all possible values of \(x^{2015} + y^{2015} + z^{2015}\).

**4)** Suppose that a function \(f:\mathbb{R} \rightarrow \mathbb{R}\) has the property that

\[f(x)^2 \leq f(y)\]

for every \(x > y\).

Prove that \(0 \leq f(x) \leq 1\) for all \(x \in \mathbb{R}\).

**5)** Prove the following inequality for all \(a, b, c > 0\).

\[\dfrac {a^2(a^3 + b^3)}{a^2 + ab + b^2} +\dfrac {b^2(b^3 + c^3)}{b^2 + bc + c^2} +\dfrac {c^2(c^3 + a^3)}{c^2 + ca + a^2} \geq 2abc\]

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest@Sharky Kesa : For question 1 my solution is as follows : The given equation simplifies to x^4+3.x^3+x^2+(3-3a)x +(a-a^2)=0. Let the roots be p,q,r,s. Now, sum of roots two at a time=1, sum of roots three at a time =(3a-3) and all four roots at a time=(a-a^2)

Now we use the identity : (pqr+pqs+prs+qrs)^2=(p^2.q^2.r^2 + .........) + 2pqrs(pq+pr+ps+qr+qs+rs) Thus we obtain the inequality : (pqr+pqs+prs+qrs)^2 >= 3pqrs(pq+pr+ps+qr+qs+rs) Substituting the values we obtain a condition : 4a^2-7a+3 >=0. Solving that we obtain that a should lie outside [3/4,1].

Please tell me whether the answer and the solution is correct or wrong.

Log in to reply

Could you provide the solutions to all questions please? So that we can reference and improve. Thanks!

Log in to reply

Using \(AM-GM\) \[a^{2}+b^{2}\geq2ab\] \[\frac{3(a^{2}+b^{2})}{2}\geq(a^{2}+ab+b^{2})\] This implies \[\frac{a^{2}(a^{3}+b^{3})}{a^{2}+ab+b^{2}}\geq\frac{2a^{2}(a^{3}+b^{3})}{3(a^{2}+b^{2})}\] Using Generalized Power mean inequality We get \[\frac{a^{2}(a^{3}+b^{3})}{a^{2}+ab+b^{2}}\geq\frac{2a^{2}(\sqrt{\frac{a^{2}+b^{2}}{2}})}{3}\] Now by \(RMS-AM\) inequality we get \[\frac{a^{2}(a^{3}+b^{3})}{a^{2}+ab+b^{2}}\geq\frac{a^{2}(a+b)}{3}\geq\frac{2a^{2}\sqrt{ab}}{3}\] Therefore \[\sum_{cyc}^{a,b,c}\frac{a^{2}(a^{3}+b^{3})}{a^{2}+ab+b^{2}}\geq\sum_{cyc}^{a,b,c}\frac{2a^{2}\sqrt{ab}}{3}\] Now using simple \(AM-GM\) on the RHS of the above inequality we get \[\sum_{cyc}^{a,b,c}\frac{a^{2}(a^{3}+b^{3})}{a^{2}+ab+b^{2}}\geq\sum_{cyc}^{a,b,c}\frac{2a^{2}\sqrt{ab}}{3}\geq2abc\]

\[\sum_{cyc}^{a,b,c}\frac{a^{2}(a^{3}+b^{3})}{a^{2}+ab+b^{2}}\geq2abc\] Hence proved .

Log in to reply

Putting \(y=0\) we get \[f(xf(0)+x)=f(x))\] \[xf(0)+x=x\] \[\boxed{f(0)=0}.........(1)\] Now we assume that there exists \(f(y)=-1\) Then putting it in original functional equation we get, \[f(0)=xy+f(x)\] \[-xy=f(x)........(2)\] now put \(x=y\) \[f(y)=-y^{2}\] But \(f(y)=-1\) Therefore \(y=1\) or \(y=-1\). Now putting these values in \((2)\) we get \(f(x)=x\) or \(f(x)=-x\) . since above two functions satisfy the given functional equation and \((1)\) Hence they are the solutions of the given functional equation.

Log in to reply

You would get 3 out of 7 for this proof. In line 2, how do you know \(f\) is injective?

Log in to reply

Proving that the function is injective is very easy. For two reals a and b let f(a)=f(b). We take two cases. In the first case put y=a and in second case put y=b. Now note that in both cases the LHS is the same. Therefore comparing the RHS you obtain that a=b. Hence function is injective

Log in to reply

Answer is right I guess (function)

Log in to reply

Log in to reply

3). let \(s_1,s_2,s_3\) be the symmetric sums. let \(p_n\) denote the nth power sum. then by newtons sum: \[\begin{array}a p_1=s_1=2\\ p_2=s_1p_1-2s_2=4-2s_2=6\Longrightarrow s_2=-1\\ p_3=s_1p_2-s_2p_1+3s_3=14+3s_3=8\Longrightarrow s_3=-2\end{array}\] so, x,y,z are roots of \[x^3-2x^2-x+2=0\] \[x^3-x-2x^2+2=x(x^2-1)-2(x^2-1)=(x-2)(x-1)(x+1)=0\] since the expression is symmetric, order doesnt matter. we have \((x,y,z)=(2,1,-1)\). put this in to get \[x^{2015}+y^{2015}+z^{2015}=\boxed{2^{2015}}\] this is the only value possible. are we suppose to expand \(2^{2015}\)?

Log in to reply

Do you think we do? Of course not! Nice solution. 7 out of 7.

Log in to reply

Is the answer to the second question is \(f(x)=0\)

Log in to reply

Log in to reply

\(\large{a \in \left(\frac{1}{24} (27-\sqrt{3}),\frac{1}{24}(27+\sqrt{3}) \right)}\)

Log in to reply

Log in to reply

\(\large{a \in \left(\frac{1}{432} (153-29 \sqrt{57}),\frac{1}{432}(153+29 \sqrt{57}) \right)}\)

Log in to reply

For roots to be real and distinct its derivative must have three distinct roots

\(4x^3+6x^2+2x+3(a-1)\).....\((1)\) And for that to happen , we again take its derivative, we get

\(12x^2+12x+2=0\)

For real and distinct roots

\(f(x_{1}) f(x_{2})<0\) where \(x_{1,2}=\frac{-3 \pm \sqrt{3}}{4}\) in \((1)\)

and then i found interval for \(a\)

Log in to reply

Log in to reply